ADOPSI INOVASI PROGRAM PEMBANGUNAN AREAL MODEL HUTAN RAKYAT DI DESA BAKAL DALAM KECAMATAN TALO KABUPATEN BENGKULU SELATAN - Asriani, Putri Suci (Jurnal AGRISEP, 2004)
The succes  of community  forest areal model  development  program  in the location  of Baka/ Da/am village,  T810 subdistrict,  South  of Bengkulu  district very depend  on wffh efective  or inefective  adoption-inovation  process  to this program.   In addition  to obsetVed  from  positif perseption   as indicated  with direct  by participant  farmers  in this program,  low or high personal  motivation partiCipant farmers  to this program,  and rank of this participation.